APLIKASI MANAJEMEN PENGOLAHAN DATA PADA PENGURUS CABANG PSSI PROVINSI D.I. YOGYAKARTA MENGGUNAKAN FRAMEWORK CODEIGNITER BERBASIS WEB - Buhari, Ahmad; Sholeh, Muhammad; Hamzah, Amir (Jurnal Jarkom, 2013)
ABSTRACT Sport is one of the factors to obtain physical healthy is directly affecting the spiritual health, as we often hear the saying "mensana incorporisano" (there is a strong body in a healthy soul). Football is one of the most popular sport among the people of Indonesia and  the world. In addition to football health reasons also serves as a medium of entertainment for all people. Along with the football has been a consumer for the wider community, whether through newspapers, radio, television, or internet. With the topic of information media of soccer competition Province Yogyakarta, the writer hopes to participate and facilitate the delivery of information found in any activities, especially football competition which was held in  Province Yogyakarta. By providing a web-based information on a regulary soccer competition in Province Yogyakarta, the user only needs to be online and access information on the web authors.Inside there are a few web authors include menu navigation information on schedules, standings table, information about football competition. By accessing this web based information a user can know the schedule of all existing match in football competition which is being rolled, and to know the statistics or rankings while we often hear "standings table". Not only information about the rolling competition alone but in this web users can find out how to join a football team or to register for the competition to be played. Keywords : information media, web, football